CARD (Comfort Ask Relax Distract) for community pharmacy vaccinations in children: Effect on immunization stress-related responses and satisfaction. (January 2023) - Taddio, Anna; Morrison, James; Gudzak, Victoria; Logeman, Charlotte; McMurtry, C. Meghan; Bucci, Lucie M.; Shea, Christine; MacDonald, Noni E.; Yang, Molly
Introduction: CARD (Comfort Ask Relax Distract) is a vaccine delivery program demonstrated to reduce pain, fear and associated immunization stress-related responses (ISRR) in children undergoing vaccinations at school. This study evaluated CARD's clinical impact when integrated into community pharmacy–based pediatric vaccinations. Methods: This was a before-and-after CARD implementation study in 5 independent pharmacies offering COVID-19 vaccinations to children aged 5-11 years. No changes were made to practices in the "before" phase. CARD interventions were integrated in the "after" phase (e.g., children prepared a coping plan using a checklist, distraction toolkits were placed in waiting and vaccination spaces, vaccinations were performed with privacy, needles were obscured). Children self-reported ISRR, including fear, pain and dizziness during vaccination, and both children and parents/caregivers (herein, parents) compared the child's experience to their last needle (better, same, worse). In the "after" phase, parents and children reported how much CARD helped (not at all, a little bit, a moderate amount, a lot). Results: The study was conducted between January 16 and March 20, 2022. Altogether, 152 children participated (71 before and 81 after CARD); demographic characteristics did not differ. Children's self-reported fear was lower after CARD, when assessed continuously (2.5 vs 3.7 out of 10; p = 0.02) or dichotomously, using a cut-off of 0 vs >0 (58% vs 80%; p = 0.01). Pain was lower when assessed dichotomously (<2 vs ≥2; p = 0.03). There was no difference in dizziness. After CARD, children and parents reported more positive experiences compared to the child's last needle ( p = 0.01, both analyses) and more children and parents reported that distraction and child participation in the process were helpful ( p < 0.001, both analyses). Overall, 92% of children and 91% of parents said CARD helped. Conclusion: CARD reduced children's fear and improved vaccination experiences for children and parents when integrated in community pharmacy–based vaccinations.